A novel coumarin‐quinone derivative SV37 inhibits CDC25 phosphatases, impairs proliferation, and induces cell death. Issue 3 (24th October 2013) - Bana, Emilie; Sibille, Estelle; Valente, Sergio; Cerella, Claudia; Chaimbault, Patrick; Kirsch, Gilbert; Dicato, Mario; Diederich, Marc; Bagrel, Denyse
Abstract Cell division cycle (CDC) 25 proteins are key phosphatases regulating cell cycle transition and proliferation by regulating CDK/cyclin complexes. Overexpression of these enzymes is frequently observed in cancer and is related to aggressiveness, high‐grade tumors and poor prognosis. Thus, targeting CDC25 by compounds, able to inhibit their activity, appears a good therapeutic approach. Here, we describe the synthesis of a new inhibitor (SV37) whose structure is based on both coumarin and quinone moieties. An analytical in vitro approach shows that this compound efficiently inhibits all three purified human CDC25 isoforms (IC50 1–9 µM) in a mixed‐type mode. Moreover, SV37 inhibits growth of breast cancer cell lines. In MDA‐MB‐231 cells, reactive oxygen species generation is followed by pCDK accumulation, a mark of CDC25 dysfunction. Eventually, SV37 treatment leads to activation of apoptosis and DNA cleavage, underlining the potential of this new type of coumarin–quinone structure. © 2013 Wiley Periodicals, Inc.